LOSING SMALL WARS : British military failure in the 9/11 Wars - Ledwidge, Frank (Yale University Press, 2017)
This new edition of Frank Ledwidge's eye-opening analysis of British involvement in Iraq and Afghanistan unpicks the causes and enormous costs of military failure. Updated throughout, and with fresh chapters assessing and enumerating the overall military performance since 2011-including Libya, ISIS, and the Chilcot findings-Ledwidge shows how lessons continue to go unlearned.